'You're in a new game and you don't know the rules: Preparing carers to care'. (October 2022) - Atkinson, Teresa; Bray, Jennifer; Williamson, Tracey
Aim: Being an informal carer for a person living with dementia can be a demanding role which can have detrimental effects on personal well-being and affect a person's ability to provide care for their loved one. This evaluation of support courses, offered by a leading UK charity dedicated to dementia family carers, highlights the impact of training to support the caring role. Setting: Participants completed booklets at the training venue and subsequently online or by post. Interviews with participants took place by telephone. Participants: 84 participants completed booklets containing measures which generated quantitative data whilst 19 family carers participated in qualitative telephone interviews. Design: A mixed methods approach was taken using booklets of validated measures to capture quantitative data, including capture of demographic information, together with semi-structured interviews conducted by telephone which were recorded, transcribed and subsequently analysed using thematic analysis. Results: Overall, both the quantitative and qualitative analysis demonstrate that attending the carers support courses had a positive impact on carers with improvements being maintained over time. Outcomes indicated that carers generally remained in a better physical, mental and emotional situation than that experienced before the course. Conclusion: Being prepared for the trajectory of the caring role when providing care for a person living with dementia can help informal carers to be better prepared, better supported and better informed. Evidence gained from this evaluation demonstrates the impact of the courses and adds to the current weak evidence base relating to dementia courses aimed at preparing carers to care.